Proceedings of the Stakeholder Workshop on The Status of Agricultural Economics in East and Southern/Central Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
The workshop was convened to discuss the status of agricultural economics in Eastern, Southern, and Central Africa. Its objectives were to: Assess the ability of academic institutions to produce well-trained M.Sc. and Ph.D. agricultural economists and to conduct research; Review existing training programs for their suitability, strengths and weaknesses, and indicate the areas needing attention;; Evaluate the market for agricultural economists, focusing on supply gaps, and provide some indicators of demand for them; and; Suggest and evaluate ways to improve agricultural economics training capacity in the region. -- from Text